Analisis Persepsi dan Kultur Masyarakat Terhadap Citra Kota Gorontalo sebagai Kota Serambi Madinah - Fitriani, Dara; Hatta, Asta Juliarman (COMPACT: Spatial Development Journal, 2024)
The city of Gorontalo is often referred to as the City of Verandas of Medina. This name refers to the religious atmosphere that exists in the lives of the residents of Gorontalo City, the majority of whom are Muslim. The religious living conditions of the residents coincide with the presence of customs which have been preserved from generation to generation in the social structure of the community. As a center of growth, Gorontalo City is a barometer of the success of Gorontalo Province's development. Development always has negative impacts if it is not managed well. Therefore, an in-depth analysis is needed regarding the elements that form the city's image that must be maintained so that customs are not increasingly marginalized in narrow spaces where pragmatic interests meet. This research is a type of descriptive research using a mix method, namely qualitative and quantitative methods. Based on the results of in-depth interviews by experts regarding the elements of city image formation discussed in the first target, it can be seen that only 4 variable elements have an influence. The variables used are regional image elements, which consist of: Path, District, Node and Landmark. Meanwhile, landmark elements in physical appearance do not characterize Islamic icons, only based on history. So it can be concluded that overall the elements that form the image of the city of Gorontalo as the City of Serambi Medina have not yet been fully formed. This nickname better describes the life of the people of Gorontalo which is based on Islam, but has not been fully realized as an image of the city. Keywords: Culture, city image, urban elements, Serambi Madinah City